Superior Capsular Reconstruction Versus Lower Trapezius Transfer for Posterosuperior Irreparable Rotator Cuff Tears With High-Grade Fatty Infiltration in the Infraspinatus. Issue 7 (June 2022) - Baek, Chang Hee; Lim, Chaemoon; Kim, Jung Gon
Background: Superior capsular reconstruction (SCR) and lower trapezius transfer (LTT) have recently been utilized to treat irreparable rotator cuff tears (IRCTs). There is still no clear guideline on which treatment method is a better fit for posterosuperior IRCTs with high-grade 4 fatty infiltration in the infraspinatus. Purpose: To compare the clinical and radiological outcomes between arthroscopic-assisted SCR (aSCR) and arthroscopic-assisted LTT (aLTT) in patients with posterosuperior IRCTs with high-grade (Goutallier grade 4) fatty infiltration in the infraspinatus muscle. Study Design: Cohort study; Level of evidence, 3. Methods: This retrospective study included patients who underwent aSCR or aLTT for posterosuperior IRCTs with high-grade 4 fatty infiltration in the infraspinatus and had a minimum follow-up of 2 years between 2017 and 2019. A total of 58 patients were divided into 2 groups according to the surgical procedure: aSCR group (n = 22) and aLTT group (n = 36). Clinical outcomes comprised the visual analog scale score for pain, active shoulder range of motion (ROM), the American Shoulder and Elbow Surgeons (ASES) score, and patient satisfaction. Radiological outcomes comprised the acromiohumeral distance (AHD). The progression of arthritis was evaluated via the Hamada grade. Graft integrity was assessed on postoperative magnetic resonance imaging scans. Results: Significant improvements in clinical outcomes were observed in both groups. However, active shoulder ROM (forward elevation: 165.7°± 22.3° vs 145.5°± 32.3°, respectively [ P = .015]; external rotation: 51.7°± 10.9° vs 41.1°± 7.0°, respectively [ P < .001]), the postoperative ASES score (84.8 ± 7.6 vs 76.8 ± 20.3, respectively; P = .045), and patient satisfaction (8.9 ± 1.2 vs 6.4 ± 2.1, respectively; P = .041) were significantly higher with aLTT than with aSCR. There was no significant difference between the groups in AHD at 2 years postoperatively. However, the rate of progression of arthritis was significantly higher with aSCR (22.7%) than with aLTT (2.8%) ( P = .027). Moreover, the graft retear rate was significantly higher with aSCR (63.6%) than with aLTT (8.3%) at 2 years postoperatively ( P < .001). Conclusion: Although aSCR and aLTT both provided improvements in overall clinical outcomes for posterosuperior IRCTs with high-grade 4 fatty infiltration in the infraspinatus, aLTT was superior in terms of functional improvement, patient satisfaction, progression of arthritis, and graft integrity. Therefore, we prefer aLTT for posterosuperior IRCTs under the condition of high-grade 4 fatty infiltration in the infraspinatus.